ANALISIS PENGARUH LINGKUNGAN KERJA, MOTIVASI KERJA ISLAM DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN KOPERASI TANI “JASA TIRTA“ SENDANG - Onky Winanda Galih Saputra, (Juremi: Jurnal Riset Ekonomi, 2023)
In this article, the focus of the research is the employees of Koperasi Tani “Jasa Tirta“ Sendang, who expects all employees to be able to work optimally to achieve the desired results. As for the purpose; 1) determine the effect of Islamic work motivation on employee performance; 2) determine the effect of the work environment on employee performance; 3) the influence of Islamic work motivation on employee performance through work discipline as an intervening variable; 4) the influence of the work environment on employee performance through work discipline as an intervening variable Koperasi Tani “Jasa Tirta“ Sendang. This study uses a quantitative approach. The population in this study were Koperasi Tani “Jasa Tirta“ Sendang, with a sample of 30 people. The sampling technique used is purposive sampling. Data collection techniques using online questionnaires via google form. The analysis tool uses SPSS 16.00. The results of the study show that: (1) Islamic work motivation has a significant direct effect on employee performance; (2) the work environment directly does not have a significant effect on employee performance; (3) Islamic work motivation indirectly has a significant effect on employee performance through work discipline (4) the work environment does not indirectly have a significant effect on employee performance through work discipline. Koperasi Tani “Jasa Tirta“ Sendang. The limitation of this research is that it only examines the effect of work motivation, work environment, and work discipline, while other variables that affect employee performance are expected to be investigated by further researchers